The Influence of Financial Literacy and Financial Self-Efficacyon Consumptive Behavior: The Moderating Role of Impulse Buying among QRIS Users in Palembang - Refa Gustia; Peny Cahaya Azwari; Muhammad Rusdi (LP2M IAIN Palopo, 2026)
The development of digital payment systems in Indonesia, particularly the use of QuickResponseCodeIndonesianStandard(QRIS),hasinfluencedchangesin people’s financial behavior, especially among the younger generation. This study aims to analyze the effect of financial literacy and financial self-efficacy on consumptive behavior in the use of QRIS with impulse buying tendency as a moderating variable. This researchemployedaquantitative approach.The research data were collected through a questionnaire distributed to respondents using an online surveymethod. The sampleconsistedof 204 Generation Z respondents who use QRIS in Palembang City selected through purposive sampling technique. The collected data were analyzed using the Structural Equation Model–Partial Least Square (SEM-PLS) method. The results show that financial literacy and financialself-efficacyhavea negativeand significanteffect on consumptivebehavior, indicatingthatthehighertheleveloffinancialliteracyandindividuals’confidence in managing finances, the lower the level of consumptive behavior. However, impulsebuyingtendencyisnotabletomoderatetherelationshipbetweenfinancial literacyandfinancialself-efficacyonconsumptivebehavior.Thisstudycontributes tothedevelopmentofliteraturerelatedtofinancialbehaviorinthedigitalpayment era and provides practical implications for improving financial awareness and better financial management.